Garner's modern English usage - Garner, Bryan A. (Oxford University Press, 2016)
Over 6000 entries With more than a thousand new entries and more than 2,300 word-frequency ratios, the magisterial fourth edition of Garner’s Modern English Usage reflects usage lexicography at its finest. It delights while providing instruction on skillful, persuasive, and vivid writing. Garner liberates English from two extremes: both from the hidebound “purists” who mistakenly believe that split infinitives and sentence-ending prepositions are malfeasances and from the linguistic relativists who believe that whatever people say or write must necessarily be accepted. The judgments here are backed up not just by a lifetime of study but also by an empirical grounding in the largest linguistic corpus ever available. In this fourth edition, Garner has made extensive use of corpus linguistics to include ratios of standard terms as compared against variants in modern print sources. No other resource provides as comprehensive, reliable, and empirical a guide to current English usage. For all concerned with writing and editing, Garner’s Modern English Usage will prove invaluable as a desk reference. Garner illustrates with actual examples, cited with chapter and verse, all the linguistic blunders that modern writers and speakers are prone to, whether in word choice, syntax, phrasing, punctuation, or pronunciation. This is the liveliest and most compulsively readable reference work for writers of our time.